Epidemiological, clinical, prognostic and therapeutic aspects of twin delivery in two referral maternity units in Dakar (Senegal) - Gassama, Omar; Mbaye, Magatte; Niass, Aminata; Boye, Diodio; Biaye, Babacar; Mbodj, Assatou; Diallo, Astou Niassy Colly; Dieme, Marie Edouard Faye (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Twin pregnancy is the simultaneous development of two embryos and then two fetuses in the uterine cavity. Objective of present study was to assess the epidemiological, clinical, prognostic and therapeutic aspects of twin delivery in two referral maternity units in Dakar. Methods: A descriptive and analytical retrospective bi-centric study of all cases of twin deliveries recorded in two referral center in Dakar was conducted during the period January 1st, 2005-December 31st, 2015, i.e. an 11-year period. It concerned 619 pregnant women who gave birth to twins in these two referral medical structures. The epidemiological parameters, clinical, prognostic and therapeutic aspects of twin childbirth were studied. The data were entered and analysed using Epi info version 3.5.3. Results: The twinning prevalence was 1.11%. The majority of our parturient women (506 or 81.7% of the cases) came from the Dakar suburbs. The average age of the parturient women was 28 years and the gestity age 3.1. Pregnancy was well monitored for 98.5% of the parturient women with an average number of prenatal consultations of 3.6. The first prenatal consultation was performed in 52% of cases in the first quarter. In more than one third of cases (234 or 37.8%), the diagnosis was made in the third quarter of pregnancy. 113 cases (18.2%) of premature rupture of membranes, 10 cases (1.61%) of threat of premature delivery and 7 cases (11.13%) of placenta previa were registered. During labour, the diagnosis was made by clinical examination in 32.2% of cases. Bichorial biamniotic twin pregnancy was the most frequent anatomical type (62.6%). On admission, the first twin (T1) was in cephalic presentation in 56.7%, in breech presentation in 15.2%; The second twin (T2) was in breech presentation in 21.1% of the cases. Caesarean section was related to the first twin in 50.6% and the second twin in 53.8% of the cases. Caesarean section was performed in 50.6% for the first twin and in 53.8% for the second twin. The mean time interval between the delivery of T1 and that of T2 was 17.4 min. Low birth weight was more frequent for the second twin (54.3%). The stillbirth rate was 48.26 per thousand. Maternal complications were dominated by renal-vascular syndromes (4.2%), haemorrhagic causes (1.86%), perineal lesions (1.6%) and uterine rupture (0.97%). Postpartum haemorrhage was observed in 8 cases (1.29%). Maternal mortality was nil Conclusions: Twin delivery poses varying difficulties due to the complexity of obstetrical mechanics and the frequency of dystocic presentations. Despite improved maternal prognosis, in recent years, perinatal mortality and morbidity, still high, remain a constant concern.